Evaluation of English 'Pediatric Basic Life Support' and 'Pediatric Cardiopulmonary Resuscitation' Videos in YouTube - Mustafa Atcı; Bedia Hanedan; Serdal Bozdoğan; Hasan Nabi Ündar; Bülent Hanedan; Osman Mücahit Tosun (Genel Tıp Dergisi)
Pediatric Basic Life Support is the initiation of cardiopulmonary resuscitation (CPR) until advanced life support is available. The American Heart Association (AHA) 2015 guideline recommend the people to perform CPR. YouTube is a video sharing site where internet users can learn about many topics, including health. Everyone can upload videos easily. Therefore, there is no control mechanism for the accuracy and up-to-dateness of the videos. Thus, there is a risk of spreading incorrect or inaccurate information. After the pediatric CPR and BLS guidelines were updated in 2015, we aimed to evaluate the quality and content of the videos published in English on YouTube. The YouTube website was searched in 15th June, 2020, using the terms “pediatric cardiac massage” and “pediatric BLS”. A total of 200 videos were evaluated.by two anesthetists in terms of instructional, content, up-to dateness and resource. 33 videos included in the study were evaluated according to Azer SA criteria. 14 videos were found to be useful and 19 of them as misleading. The average total viewing times and daily viewing numbers of useful videos were found to be higher. When evaluated in terms of content, similar results were obtained in both groups. This shows that viewers value videos more being educational than content. For this reason, we think that while editing videos, Azer criteria should be taken into account as an objective criterion and their content should be prepared according to current guidelines.